245 A PILOT STUDY EVALUATING USE AND ACCEPTABILITY OF A NATIONAL AUDIT TOOL AND MANUAL FOR PSYCHOTROPIC MEDICATIONS IN RESIDENTIAL CARE. (25th October 2022) - Allen, Y; Timmons, S
Abstract: Background: Psychotropic medications are frequently prescribed for long-term care residents, even though the risks frequently outweigh the benefits. A draft tool was developed for self-audit of the appropriateness of psychotropic medications prescribed for non-cognitive symptoms for people with dementia in Residential-Care Facilities (RCF). Prior to national use, the audit tool, audit manual and training required piloting. Methods: The case notes of ten residents with dementia were selected at random within a single RCF. A set of notes were audited by professional staff after online (pre-recorded) audit training, with subsequent feedback by the auditors on the process via focus groups/individual interviews. A second set of notes were then audited, with feedback via a brief survey. Results: All auditors (7 nurses, 4 doctors, and 4 therapists) gave feedback via a focus group(n=4) or 1:1 interviews; 7 also completed the second-round survey. The pre-audit online training was welcomed but some auditors required additional support during the audit, especially if inexperienced or if there was a gap between training and audit performance. Improvement suggestions for the audit manual included shortening it; adding a glossary of terms, and additional information for decisions on the appropriateness of "as needed" (PRN) medications. Auditors reported difficulties with reading handwriting, locating information in the chart, and determining if a medication was newly or previously prescribed on occasion (due to inconsistencies with prescribing documentation). Conclusion: Overall, the feedback was positive; all reported that the audit was relevant to their practice, and the manual and online training were useful. Future audits could be facilitated by electronic prescriptions, protected time to complete audits, and site audit leads (senior nursing or medical staff who are familiar with the residents, the audit topic, and with performing the audit). Inexperienced auditors should have, in addition to a training session, a supported auditing session.